Nueva Clasificación de la enfermedad periodontal - García Linares, Sixto (2003)
The periodontal disease was classified in the 1999 Workshop according to concepts that attempt to clarify certain confusing points of view found in the 1989 classification. Here it is revised all the improvements made to this classification pointing out the advantages of this new and modem approach to periodontal disease.